2016
DOI: 10.3126/jmrd.v2i1.16212
|View full text |Cite
|
Sign up to set email alerts
|

Maize production in mid hills of Nepal: from food to feed security

Abstract: This study was undertaken in 2016 to analyze the production and utilization of maize in Nepal. Sixty maize growers from Kavre and Lamjung districts were selected using purposive, cluster and simple random sampling techniques. Similarly, six feed industries and five maize experts from Chitwan district were also interviewed. Study shows 56% of the total areas were used for maize production and 50% of the maize areas were covered by hybrid maize. There was no practice of contract maize production. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…In the street market, the use of green cobs roasted as a favorite snack food is increasing tremendously. Out of total maize produced in the hills, only 55-60 percent and 30-35 percent are used for feed and human food respectively while more than 80 percent of maize produced in Terai is used for feed and 15-20 percent for human consumption [12,13]. This figure illustrates how yellow and white maize are primarily connected to society's livelihoods.…”
Section: Discussionmentioning
confidence: 99%
“…In the street market, the use of green cobs roasted as a favorite snack food is increasing tremendously. Out of total maize produced in the hills, only 55-60 percent and 30-35 percent are used for feed and human food respectively while more than 80 percent of maize produced in Terai is used for feed and 15-20 percent for human consumption [12,13]. This figure illustrates how yellow and white maize are primarily connected to society's livelihoods.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Nepal, the importance of maize increase with altitude, eventually standing as a staple crop in northern part of the country (KC et al, 2015). In the context of world, 58% of maize is utilized in animal feed, 16% in human food and 26% in bioethanol production (HLPE, 2013), whereas, study shows that 60%, 25% and 3% of grain were used for animal feed, food and seed respectively in the hilly district of Nepal and rest is sold to the traders (Timsina et al, 2016). Mainly, organic manure (FYM), urea, green manure and recently some kinds of biofertilizer are being used as the source of nitrogen in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, appropriate extension services are needed for the adoption of developed hybrids. Timsina et al (2016) also used two independent samples t-test to compare the yield of maize in Kavre and Lamjung districts of Nepal, which revealed that the productivity of maize was significantly higher in kavre (4.63 t/ha) compared to Lamjung (3.2 t/ha). In addition, the average yield of maize (both hybrid and open pollinated improved improved varieties) in Kavre was calculated 4.63 t/ha, while the average yield of only hybrid varieties was calculated 5.06 t/ha; this showed the superiority of hybrids over improved in terms of yield.…”
Section: Mean Comparison Of Productivity Of Hybrid and Op Improved Mamentioning
confidence: 99%